Effect of lead and chromium on germination and seedling growth of tomato (Solanum lycopersicum) and eggplant (Solanum melongena) - GAUTAM, MAMTA; SINGH, ANIL KUMAR; JOHRI, RAJIV MOHAN (The Indian Journal of Agricultural Sciences, 2015)
A study was conducted to determine the effect of different concentrations of lead and chromium on seed germination and seedling growth of tomato (Solanum lycopersicum L.) and eggplant (Solanum melongena L). Seeds were grown under laboratory conditions at five concentration levels each of Pb (0, 2.5, 5.0, 7.5 and 10 ppm) and Cr (0, 0.1, 0.5, 2.5 and 7.5 ppm). Both lead and chromium treatments showed toxic effects on various growth indices of tomato and eggplant. The results of the present study have indicated that as Pb concentration increased from 0 to 5.0 ppm, the germination percentage, plumule and radicle length, fresh and dry weight decreased in tomato from 94 to 19%, 6.78 to 0.88 cm, 5.77 to 1.16 cm, 0.49 to 0.10 mg and 0.05 to 0.01 mg, respectively, while in eggplant, the decrease in the corresponding parameters was from 93 to 20%, 5.76 to 1.23 cm, 5.20 to 1.89 cm, 0.46 to 0.11 mg and 0.05 to 0.01 mg, respectively. In case of Pb, the tomato and eggplant seedlings did not germinate at 7.5 to 10 ppm concentrations. A similar trend was observed for germination and seedling growth parameters in case of Cr at 7.5 ppm concentration. On the basis of the results obtained, it was concluded that tomato was more sensitive than eggplant. As far as the relative response to the two heavy metals is concerned, it was clear that lead is less toxic than chromium. The uptake of lead by plant is also very low. An attempt was made to quantify the response of the seedlings of the two crops to varying Pb and Cr concentrations. The models used were linear, quadratic, and polynomial of degree 3. The responses could be described very satisfactorily by the polynomial of degree three with R2> 99% for all the parameters.